Adoption and impact of natural farming practices in batticaloa district - Thivahary, G.; Viharnaa, R. (university of Jaffna, 2020)
The practice of natural farming system significantly reduces the production costs. Currently, natural farming system is practiced by farmers in various parts of Sri Lanka. A substantial number of smallholder farmers from Vaharai region of Batticaloa district engaged in natural farming. A questionnaire survey was carried out among randomly selected farmers practicing natural farming and not practicing natural farming in Vaharai region to compare the famer's perception on the impact of natural farming practices on soil fertility, soil erosion and labour input. The results revealed that mainly the women-headed families engaged in natural farming system in the study area. The practices like, ploughing, mulching, usage of compost, reduced usages of chemical fertilizer, chemical insecticides and chemical herbicides were highly adopted by farmers practicing natural farming. Moreover, according to famer's perception,the natural farming practices significantly improved the soil fertility and reduced soil erosion in the region.
Keywords: Adoption; Compost; Farming; Soil fertility